Optimization of stochastic EUV resist models parameters to mitigate line edge roughness - Biafore, John J; Latypov, Azat; Chunder, Anindarupa; Brendler, Andy; Bailey, Todd; Levinson, Harry J (SPIE, 2017)
The optimization problem of reducing EUV line edge roughness (LER) of a given feature, subject to the tolerance constraints on a CD of this feature at nominal EUV process conditions and several off-nominal conditions, is formulated. A stochastic rigorous Monte-Carlo EUV resist model is employed to solve this stochastic optimization problem. Several options for optimization algorithms, suitable for the solution of the formulated EUV LER optimization problem, are presented and discussed, along with the results of their tests.